2016
DOI: 10.1590/1983-21252016v29n329rc
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of Vernalizated Semi-Noble Garlic Cultivars in Western Rio Grande Do Norte State, Brazil

Abstract: -Garlic is a vegetable that has economic and social relevance in Brazil. Rio Grande do Norte is among the consumer states, however, despite having regions with favorable conditions for growing garlic, it depends on imports of this product to meet its demand. The introduction of cultivars that have high yield and quality, and the adjustments in vernalization technology, which is a key issue for adaptation of new cultivars, are mechanisms that can contribute to garlic revitalization in areas previously producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 8 publications
1
16
1
3
Order By: Relevance
“…The authors stated that edaphoclimatic conditions and agronomic practices highly affect the yield of garlic culture. Lucena et al (2016) compared quality characteristics of semi-noble garlic cultivars subjected to different bulb-seed, pre-planting vernalization periods in two municipalities of the Western Mesoregion of Rio Grande do Norte State. The authors observed differences in the behavior of genotypes in relation to the bulb diameter in the two locations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors stated that edaphoclimatic conditions and agronomic practices highly affect the yield of garlic culture. Lucena et al (2016) compared quality characteristics of semi-noble garlic cultivars subjected to different bulb-seed, pre-planting vernalization periods in two municipalities of the Western Mesoregion of Rio Grande do Norte State. The authors observed differences in the behavior of genotypes in relation to the bulb diameter in the two locations.…”
Section: Resultsmentioning
confidence: 99%
“…The first record of growing garlic date 4000 years ago, since then has become one of the most popular crop worldwide, both as a medicine and a vegetable, being China the chief producer of garlic in the world and Brazil the largest importer (Chen et al, 2013;Lucena et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A região possui clima tropical chuvoso, do tipo Aw, de acordo com a classificação de Köppen-Geiger, com temperatura média anual em torno dos 23°C e índi-ce pluviométrico de aproximadamente 1.100 mm por ano, concentrados entre os meses de fevereiro a maio. A BRS Hozan é uma cultivar de alho comum, que possui bulbos com formato irregular e não necessita de vernalização para produzir bulbos em regiões tropicais (Honorato et al, 2013;Lucena et al, 2016a;. A Roxo Pérola de Caçador pertence ao grupo dos alhos nobres, de ciclo tardio, e possui bulbos redondos e grandes .…”
Section: Materiais E Métodosunclassified
“…Variáveis como pH, acidez titulável, sóli-dos solúveis, relação sólidos solúveis/acidez titulável, açúcares solúveis totais, sólidos totais, pungência, ín-dice industrial, dentre outros, são importantes para a determinação da qualidade do alho (Soares, 2013;Lopes et al, 2016a;Lucena et al, 2016a).…”
unclassified
See 1 more Smart Citation